AGEN CERDAS PINTAR IPA UNTUK SEKOLAH MENENGAH PERTAMA (SMP) KELAS 3 - Nining Suryani (Universitas Bina Sarana Informatika Kota Sukabumi, 2016)
School is one institution that has the duty and function to seek, promote and foster the potential of thestudents. Various factors affect the quality of education among which is the curriculum, instructionalmedia, learning and other methods can also give effect to student interest. Students' interest often affectstudent learning outcomes, with interest in learning the low is likely to produce learning outcomes thatare not optimal, in addition to the above lack of student interest is also influenced by the learning methodthat teachers are still using a system of conventional teaching by means lecture. The results ofobservations at one junior high school students to the data values are still many students who get lowmarks, especially in science subjects. This is caused by boredom experienced by the students of theatmosphere in the classroom, as well as the delivery of content media pembelajaan unattractive anddifficult to be understood by the students. So in need of a new system that can support teaching andlearning activities, one of which is interactive learning with intelligent agent-based animation. Thislearning system using multimedia development cycle by Mc Leod.